A Parallel Tabu Search Algorithm for Optimizing Multiobjective VLSI Placement - Minhas, Mahmood R. (2005)
Abstract. In this paper, we present a parallel tabu search (TS) algorithm for efficient optimization of a constrained multiobjective VLSI standard cell placement problem. The primary purpose is to accelerate TS algorithm to reach near optimal placement solutions for large circuits. The proposed technique employs a candidate list partitioning strategy based on distribution of mutually disjoint set of moves among the slave processes. The implementation is carried out on a dedicated cluster of workstations. Experimental results using ISCAS-85/89 benchmark circuits illustrating quality and speedup trends are presented. A comparison of the obtained results is made with the results of a parallel genetic algorithm (GA) implementation.